Pengaruh Servicescape Terhadap Minat Beli Pada Gubuk Resto & Steak Kota Bima - Neneng Fathona; Amirulmukminin Amirulmukminin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Servicescape gives a positive or negative impression as a reference in managing it more effectively. With the servicescape, cafe and restaurant business people can provide good quality services for consumers to feel comfortable while in cafes and restaurants and influence on buying interest. Steak in Bima City. The type of research used is associative. The population used is all consumers of Resto & Steak Huts whose numbers are not known with certainty (unknown population), so the sample size used is 96 samples. All samples were given a questionnaire with a Likert scale. Data collection techniques used are observation, interviews, questionnaires and literature studies with data analysis techniques used are validity, reliability, simple linear regression analysis, simple correlation t test and determination test. From the results of data processing and analysis states that servicescape does not affect consumer buying interest in the Resto & Steak Hut in the City of Bima with a t value of -0.556 and a significance value of 0.580, and the results of the determination test show that Servicescape influence on Buy Interest in the Hut Bima City Restaurant & Steak is 0.007 or 0.7% only. while the remaining 99.7% is influenced by other factors not examined in this study